2001
DOI: 10.1161/01.str.32.8.1832
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Tissue Plasminogen Activator and Inpatient Mortality Rates for Patients With Ischemic Stroke Treated in Community Hospitals

Abstract: Background and Purpose-Most analyses of intravenous tissue plasminogen activator (IV tPA) use for acute stroke in routine practice have been limited by sample size and generally restricted to patients treated in large academic medical facilities. In the present study, we sought to estimate among community hospitals the use of IV tPA and to identify factors associated with the use of IV tPA and inpatient mortality. Methods-We evaluated a retrospective cohort of 23 058 patients with ischemic stroke from 137 comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
160
3
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(181 citation statements)
references
References 50 publications
14
160
3
4
Order By: Relevance
“…We found no difference in the occurrence of SICH and early in-hospital mortality between the sub-3 h and 3-4.5 h groups. We observed a similar incidence of SICH (5.7%) and early in-hospital mortality (9.7%) in thrombolysis up to 4.5 h as were reported in the NINDS study [1] and other t-PA registries [7,[12][13][14][15][16][17][18][19], where most patients were treated within 3 h. In the ATLANTIS trial [4], 7.0% of the t-PA treated patients in the 3-5 h time window had a SICH, compared to 5.3% in our cohort.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found no difference in the occurrence of SICH and early in-hospital mortality between the sub-3 h and 3-4.5 h groups. We observed a similar incidence of SICH (5.7%) and early in-hospital mortality (9.7%) in thrombolysis up to 4.5 h as were reported in the NINDS study [1] and other t-PA registries [7,[12][13][14][15][16][17][18][19], where most patients were treated within 3 h. In the ATLANTIS trial [4], 7.0% of the t-PA treated patients in the 3-5 h time window had a SICH, compared to 5.3% in our cohort.…”
Section: Discussionsupporting
confidence: 86%
“…A substantial number of ischemic stroke patients may benefit from intravenous t-PA treatment by extending the time window to 4.5 h. In our cohort, about 1 in 5 of all admitted ischemic stroke patients were treated with t-PA, which is a higher proportion than reported in previous studies [7,13,15,16,18].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar studies looking at delays in New York and in the Stroke Belt did not find an association between ethnicity and delay [75,76], whereas another study conducted in San Diego detected a trend toward delayed presentation among blacks [77]. Also, blacks were less likely to receive intravenous tPA [78,79]. Although delays in presentation and contraindications were seen more frequently in blacks, these were not statistically significant from whites [78].…”
Section: Effect Of Race Ethnicity On Outcomesmentioning
confidence: 95%
“…Some previous studies have shown that black patients receive IV rt‐PA 1/5 to 3/4 as often as white patients,8, 9, 21, 22, 23, 24 but other studies have reported no difference in rates of treatment 25, 26. Data for Hispanic patients are also conflicting.…”
mentioning
confidence: 97%